Analysis Of The Current Overview in Distribution Management and Marketing Channels: Strategies Challenges and Innovations - Rivai, Andi Muhammad; Nurmasnaeni, Nurmasnaeni; Jannah, Nadilah Zahratul; Resky, Nur Amalia; Anwar, Yusri (Universitas Negeri Makassar, 2024)
This journal provides a contemporary overview of distribution and marketing channel management, addressing related strategies, challenges, and innovations. The article delineates recent developments in efforts to enhance distribution efficiency and marketing channel effectiveness amidst the continually evolving market dynamics. Newly proposed and implemented strategies by various companies are presented, along with an analysis of the key challenges faced in managing distribution and marketing channels. Furthermore, technological innovations playing a pivotal role in improving operational performance are discussed. By detailing these concepts, this journal offers profound insights to readers on current trends and future directions in distribution and marketing channel management.